Analisa Kondisi Geologi berdasarkan pemetaan permukaan Daerah Kebagoran Kabupaten Kebumen Jawa Tengah - Arica Nefia; Uyu Saismana; Marselinus Untung D (Lembaga Bale Literasi, 2025)
Analysis of Geological Setting based on surface mapping of Kebagoran Area, Kebumen Regency, Central Java: Kebumen is an area of subduction that originally served as an ocean floor, which later emerged due to the collision of two tectonic plates around 117 to 60 million years ago, specifically the Eurasian continental plate and the Indian oceanic plate Asikin.S. (1992). The Kebagoran area in Pejagoan Subdistrict, Kebumen Regency, Central Java Province, is an area consisting of hills and plains that extend in a generally west-east direction, and is within the South Serayu Mountains Zone. Research on geological conditions to determine several aspects, namely including geomorphology, stratigraphy, and geological structure, locally. The research method used is by conducting surface mapping, laboratory and studio analysis stages. surface mapping by taking direct measurements in the field, laboratory analysis using thin incisions of rocks and micropaleontology, studio analysis by analyzing data and making maps. The geology of the study area has two types of geomorphological units based on morphogenesis, namely homocline hills geomorphology unit and alluvial deposits geomorphology unit. Based on lithostratigraphy, the rock units are divided into five different units based on age, from the oldest to the youngest. The geological structure in this area consists of faults with horizontal type.